Korean Drama Influence on Communication Styles of Female Students at Nawwir Qulubana Islamic Boarding School - Sam'ani, yatimah, Melinda nur khasanah; Muhammad Yusuf (Journal of Communication Studies, 2025)
This research investigates shifts in communication styles among female students at Pondok Pesantren Nawwir Qulubana Wonosobo, driven by Korean dramas. The rising appeal of K-Dramas in Indonesia highlights a clash between pesantren principles of modesty and politeness and the emotive Korean ways of speaking. Employing a qualitative phenomenological method, the study delves into how these students balance Korean pop culture with pesantren traditions. Findings reveal that female students incorporate Korean terms like "omo," "ne," "eonni," and "gomawo" into everyday talk via reflective "Me" and impulsive "I" aspects. Yet, they uphold pesantren standards by thoughtfully adapting culture, mentally filtering Korean elements for suitable contexts. Such expressions are used only in casual settings, not formal ones. The pesantren's shared living space accelerates the adoption of Korean language. Ultimately, Korean media doesn't supplant pesantren values but acts as a means of personal expression, safeguarding Islamic identity and pesantren customs